A new model of bauxitization in quartzitic landscapes: A case study from the Southern Espinhaço Range (Brazil) - De Campos, Daniela S.; Monteiro, Hevelyn S. [UNESP]; Vasconcelos, Paulo M.; Farley, Kenneth A.; Silva, Alexandre Christófaro; Vidal-Torrado, Pablo (Wiley, 2023)
Lithology plays a fundamental role in rock weathering and erosion, and in landscape evolution. When weathering- and erosion-prone lithologies are protected from erosion by more resilient rock types (e.g., quartzites and banded iron formations) unusual weathering products result. At the Southern Espinhaço Range, Minas Gerais, Brazil, bauxitic weathering profiles are found in a unique geomorphological–lithological–climatic setting. Resistant quartzites acted as a barrier against erosion of interbedded hematite-phyllite lenses, channelling solution flows and facilitating the formation of deep weathering profiles. The long-term exposure of the hematite-phyllites under alternating wet and dry tropical climates favoured widespread bauxitization. Here we investigate the geochemical, mineralogical, geochronological and micromorphological signatures of scaffolded bauxites in order to reconstruct their evolutionary history. Our data suggest that recurrent aluminium and iron mobilization within the profiles were mainly driven by mineral dissolution-reprecipitation mediated by bioturbation and the influx of vegetation-derived organic species. (U–Th)/He geochronology of Al-goethite reveals that bauxitization started at least since the Lower Miocene, with important intensification of weathering in the Upper Miocene and Lower Pleistocene. The adjacent resilient quartzites acted as scaffolds for bauxitization and supported the preservation of more erodible weathering profiles developed over phyllites. Surface waters that could not infiltrate into the impermeable adjacent quartzites preferentially infiltrated into the more weathereable phyllites, enhancing their porosity and permeability, further enhancing weathering. The evolutionary history of Southern Espinhaço Range bauxites suggests a new model of bauxitization in ancient land surfaces evolution underlain by quartzites, where erosion-prone lithologies are scaffolded by resilient quartzites and survive long-term weathering with minimum erosion, producing bauxites.
Keywords: (U–Th)/He geochronology; ancient landscape evolution; bauxitic duricrust; bauxitization scaffolding model; strength bedrock